Use of dogs as security instruments in the municipalities of Peru: Period 2016-2020 - Barinotto S., Claudia (2023)
The aim of this study was to quantify the dogs that were used as security instruments in the surveillance service provided by the security service and the municipalities of Peru, between the years 2016 to 2020. For this, the information available in the National Registry of Municipalities, prepared by the National Institute of Statistics and Informatics (INEI) was used. The result was that at the provincial level there was a greater proportion of municipalities where the serenazgos used dogs and that the years 2016 and 2017 were the years where there was a greater number of dogs used as a security element in provincial and district municipalities. It was also found that Lima was the department that had the highest number of dogs registered as a security element, followed by Callao, Piura, La Libertad and Cusco respectively. Finally, it was observed that, of the districts of Metropolitan Lima, Lima Cercado, Santiago de Surco, San Borja, Chorrillos and La Molina, they were those with the largest number of dogs as a security element for the serenazgo.